Introduction to Literature With Storyling Method For Early Children in The Pojok Village Library, Mojogedang, Karanganyar - Fitri Sulistiyarini (UIN Raden Mas Said Surakarta, 2022)
Abstract This study aims to determine whether the method used in the introduction of literacy in early childhood in the village of Corner, Mojogedang, Karanganyar is appropriate or not, knowing the steps taken in the introduction of literacy in early childhood, the media and methods used, as well as the benefits. which is obtained by the children through the development of the corner village library through the introduction of literacy activities with the storytelling method. The method used in this study is a qualitative approach, using the method of collecting data through participatory, observation, documentation and interviews. The data found in the field is that there are problems related to the lack of interest and knowledge of early childhood about literacy and village libraries that are poorly maintained and have not been operating for several months. The results of the study show that: 1) the introduction of literacy is still understood as an activity that only reads and writes, while actual literacy includes many linguistic activities, 2) the method used to attract children's attention uses the storytelling method with the selection of animals as characters, 3) children are interested in village library development activities through the introduction of literacy for early childhood, so that these activities succeeded in attracting children's attention with evidence that children were enthusiastic in participating in activities. Key Key : Literacy, storytelling method, library, early childhood.